New Keynesian Macroeconomics: Empirically tested in the case of Republic of Macedonia - Dushko Josheski; Darko Lazarov (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
In this paper we test New Keynesian propositions about inflation and unemployment trade off with the New Keynesian Phillips curve and the proposition of non-neutrality of money. The main conclusion is that there is limited evidence in line with the New-Keynesian theory. Money and growth are cointegrated series and that money growth influences the economics growth with one quarter lag. Cointegration means also that if the two series are cointegrated they have long run equilibrium. St.Louis model in the paper showed overall that increase in money growth leads to decrease in the economy growth. But the effect in the equation at three quarters lag is positive. The NAIRU rate in the unemployment inflation trade off model is almost similar as high to the actual unemployment. In the New Keynesian Phillips curve not surprisingly, there appears to be no statistically significant relationship between inflation and unemployment – even in the classical Philips curve and in adaptive expectations Philips curve by Modigliani-Papademos (1975). Or the Friedman-Phelps-Lucas expectations augmented one between the difference of actual and expected inflation rate and the gap between actual and the natural rate of unemployment presented in the next equation.
Keywords: B22; B23; 330; New-Keynesian Macroeconomics; NAIRU